Results and Performance of the World Bank Group 2012 : Volume I - Independent Evaluation Group (Washington, DC: World Bank, 2013)
After a sustained period of considerable achievement in poverty reduction, developing countries are now navigating an increasingly uncertain time. Developing countries overall are estimated to have achieved, ahead of schedule, the Millennium Development Goal (MDG) of cutting the 1990 rate of extreme poverty in half. The global development context has direct implications for the World Bank Group's clients, and ultimately for the World Bank Group itself. The Bank Group delivered a large-scale response to the global financial crisis of 2008-09. The portfolio of the Multilateral Investment Guarantee Agency (MIGA) became highly concentrated in the financial sector in the Europe and Central Asia region during the crisis, but the agency has made progress in diversifying its portfolio since FY11. The country program, as defined in a country assistance (or partnership) strategy, is an important intersection point for the activities of the three Bank Group institutions. Since the 2008-09 crises, Bank Group support for reforms to expand economic opportunities has been particularly relevant. The increasing concentration of International Finance Corporation (IFC) and MIGA portfolios in the financial sector gives rise to both opportunities and challenges. Crises, ratings for development policy operations remained high.